Penerapan Kontrol Suhu PID pada Pembuatan Biodiesel dari Minyak Jarak (Ricinus Communis) dengan Katalis Koh (0,75%, 1% W/W) dan ZNO (0,7%, 0,8% W/W) - Nikolaus Dharmawan Dharsono; Rifki Hermana; Slamet Supriyadi (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
Biodiesel is an alternative fuel derived from renewable sources, one of which is castor oil. In previous studies, the biodiesel production process at the laboratory scale was still carried out using manual heating with an electric stove. In addition, earlier research generally used only single type of catalyst, either KOH or ZnO. To overcome the limitations of manual temperature control, this study applies  temperature control system using  PID autotuning autonics controller to automate temperature reaction. This research apply  further modification by combining KOH  (0.75% w/w and 1% w/w) with ZnO  (0.7% w/w and 0.8% w/w) in the production of biodiesel from castor oil. The research aims to optimize biodiesel yield through the application of a PID-based temperature control system in the transesterification reaction using various catalyst combinations. The resulting biodiesel (B30) from the transesterification process is then tested directly on a diesel engine . The temperature control results using the autonics controller produced PID parameters of P = 4.3, I = 208 s, and D = 36 s. The temperature control system response shows  overshoot of 61 °C, rise time of 16 minutes,  settling time of 24 minutes, and  steady-state error of 0.6 °C. The PID temperature control can replaced manual control by providing a more stable temperature and eliminating reliance on manual adjustments. The highest biodiesel yield was obtained using a combination of 1% w/w KOH and 0.7% w/w ZnO catalysts reaching 91.25%. Interaction between KOH and ZnO tended to reduce yield, indicating that KOH is less suitable when used directly together with ZnO. The biodiesel consumption from the reaction is 270 ml/hour which is lower than that of biosolar at 300 ml/hour.